Effects of Small Hydropower Stations Along Rivers on the Distribution of Aquatic Biodiversity - Gu, Peng; Zhang, Zhaochang; Liu, Jing; Wang, Tao; Xiao, Yunxing; Yu, YangJinzhi; Miao, Hengfeng; Zhang, Yumiao; Liao, Fei; Yang, Kunlun; Li, Qi (Frontiers in Ecology and Evolution, 2022)
At present, there is little research on the impact of small hydropower stations on aquatic biodiversity. In order to investigate whether the existence of small hydropower stations has a significant impact on the aquatic biodiversity of their watersheds, we conducted a systematic study on the abundance of plankton, benthic animal, fish and microorganism in the watersheds of 15 small hydropower stations in Qionglai City. The results showed that 59 species of phytoplankton from 3 divisions, 16 species of zooplankton from 4 categories, 25 species of benthic animal from 3 phyla and 30 species of fish were found in the study basin. The analysis of the physical and chemical indicators of water bodies and the distribution characteristics of aquatic organisms found that the operation of small diversion-type power stations in Qionglai City changed part of the aquatic habitat in the basin, with a greater impact on the activities of large aquatic animals (fish) and a smaller impact on plankton and microorganism, and the intensity of the impact was shown as fish > benthic animal > plankton > microorganism. The small hydropower stations in this study have an impact but not significant on the aquatic biodiversity in the Baimo and Wenjing River in the Qionglai City, and this study provides a data reference for the comprehensive assessment of the environmental impact of small hydropower stations.